Briefwechsel und Lebenszeugnisse : kritische Edition mit Übersetzung - Opitz, Martin, 1597-1639 (De Gruyter, 2009)
Martin Opitz (1597-1639) is regarded as one of the moving forces behind the rise of German literature in the 17th century. Most of his correspondence, however, was written in Latin. Now in this three-volume work his letters have been collected, edited, translated and provided with detailed annotations for the first time, and supplemented with inscriptions and dedications, together with contemporary reports and documents about the poet. This work is of great significance for the history of German and European culture; it is richly illustrated, with an introduction, and apart from tools for text.